The paradox of Latin American integration - Rosell Medina, Mónica (2022)
Since its inception, Latin America has been, through its most illustrious thinkers, a focus of the regional integration in the world. Even though the ideas which, eventually, would inspire other thinkers elsewhere in the world to undertake their own integration projects are widely accepted and supported in the region, attempt after attempt for a Latin American integration has failed, either because of intrinsic or extrinsic motives, under its control or otherwise. The author, through a historical and economic analysis of the different Latin American integrationist initiatives tries to find the common denominator which has prevented the majority —if not all— of those projects from achieving their objective: a united America. She also studies the distinction and —apparent— conflict between supranationalism and intergovernmentalism, and how both models have led the projects which applied them to success or failure. The author concludes that it is a combination of factors, including the subscription of free trade agreements which, rather than integrating the region, isolate their signatories one from another; the regional idiosyncrasy and its nationalist aspirations which come and go; and the initiatives themselves which have gradually entangled its members, since they force them to decide whether to follow the directives of one or the other, which until now have impeded the real integration of the Latin American countries.